Morphofunctional model characteristics of ice hockey players across different playing positions - Morozov, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to examine and substantiate model morphofunctional characteristics of ice hockey players across different playing positions. Results and conclusions. As a result of analysing the height indicators of young ice hockey players with regard to the player’s position, it was revealed that the shortest players are goalkeepers; however, these values are not statistically significant, as the sample for this position was small. Forwards possess higher body length indicators. Long-term preparation of young ice hockey players is impossible without knowledge of the morphofunctional characteristics of body development. The development of model characteristics is a priority task in organising the training process of young players in ice hockey across different positions, which creates all the necessary conditions for improving sporting mastery in training and competitive activities.